Soybean Yellow Stripe-like 7 is a symbiosome membrane peptide transporter important for nitrogen fixation. Issue 1 (5th February 2021) - Gavrin, Aleksandr; Loughlin, Patrick C; Brear, Ella; Griffith, Oliver W; Bedon, Frank; Suter Grotemeyer, Marianne; Escudero, Viviana; Reguera, Maria; Qu, Yihan; Mohd-Noor, Siti N; Chen, Chi; Osorio, Marina Borges; et al.
Abstract: Legumes form a symbiosis with rhizobia that convert atmospheric nitrogen (N2 ) to ammonia and provide it to the plant in return for a carbon and nutrient supply. Nodules, developed as part of the symbiosis, harbor rhizobia that are enclosed in a plant-derived symbiosome membrane (SM) to form an organelle-like structure called the symbiosome. In mature nodules exchanges between the symbionts occur across the SM. Here we characterize Yellow Stripe-like 7 (GmYSL7), a Yellow stripe-like family member localized on the SM in soybean ( Glycine max ) nodules. It is expressed specifically in infected cells with expression peaking soon after nitrogenase becomes active. Unlike most YSL family members, GmYSL7 does not transport metals complexed with phytosiderophores. Rather, it transports oligopeptides of between four and 12 amino acids. Silencing GmYSL7 reduces nitrogenase activity and blocks infected cell development so that symbiosomes contain only a single bacteroid. This indicates the substrate of YSL7 is required for proper nodule development, either by promoting symbiosome development directly or by preventing inhibition of development by the plant. RNAseq of nodules where GmYSL7 was silenced suggests that the plant initiates a defense response against rhizobia with genes encoding proteins involved in amino acid export downregulated and some transcripts associated with metal homeostasis altered. These changes may result from the decrease in nitrogen fixation upon GmYSL7 silencing and suggest that the peptide(s) transported by GmYSL7 monitor the functional state of the bacteroids and regulate nodule metabolism and transport processes accordingly. Further work to identify the physiological substrate for GmYSL7 will allow clarification of this role. Abstract : Soybean Yellow Stripe-like 7 encodes an oligopeptide transporter that localizes to the symbiosome membrane in nodules and contributes to nitrogen fixation and symbiosome development.